2013
DOI: 10.1016/j.jaging.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Hearing the voices of people with high support needs

Abstract: This article draws on findings from a study commissioned by the British charity, The Joseph Rowntree Foundation, to explore the needs and aspirations of older people who for whatever reason require a high degree of assistance. The study explored the personal aspirations of a small diverse sample (n=26) of hitherto un-researched people living in different parts of the UK. Most were over 85 years of age, with varied ethnicity, health status, social care needs, financial status and lifestyle. Many participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…They showed remarkable resilience to manage the losses they had experienced throughout their life and in developing new relations (Nicholson, Meyer, Flatley, & Holman, ). Similar findings emerged in another study conducted in the UK, which highlighted that older persons accepted that some of their aspirations might not be realistic (Katz, Holland, & Peace, ). A Swedish study aimed at exploring frail older persons' experiences of health found that feeling assured and capable was of central importance to participants' sense of well‐being.…”
Section: Introductionsupporting
confidence: 83%
“…They showed remarkable resilience to manage the losses they had experienced throughout their life and in developing new relations (Nicholson, Meyer, Flatley, & Holman, ). Similar findings emerged in another study conducted in the UK, which highlighted that older persons accepted that some of their aspirations might not be realistic (Katz, Holland, & Peace, ). A Swedish study aimed at exploring frail older persons' experiences of health found that feeling assured and capable was of central importance to participants' sense of well‐being.…”
Section: Introductionsupporting
confidence: 83%
“…Nicholson, Meyer, Flatley, Holman, and Lowton ( 2013 ) described how the frail elderly experienced loss of autonomy and functional capacity, but they also reported creativity in handling the shortcomings from a life with frailty. Other studies exploring the experience of daily life of community-dwelling frail elderly showed that their experiences varied, but at the same time it seemed that the frail elderly in general experience different kinds of struggles in relation to management of daily life (Haak, Malmgren Fange, Iwarsson, & Dahlin-Ivanoff, 2011 ; Katz, Holland, & Peace, 2013 ; Tollén, Fredriksson, & Kamwendo, 2008 ; Van Campen, 2011 ; Ebrahimi, Wilhelmson, Eklund, Moore & Jakobsson, 2013 ; Ebrahimi, Wilhelmson, Moore & Jakobsson, 2012 ; Nicholson, Meyer, Flatley, Holman & Lowton, 2012 ).…”
mentioning
confidence: 99%
“…Nevertheless, our research shows that the physical and cognitive limitations, especially the difficulties of dealing with an ageing body in daily activities, provide the main barriers to discuss quality of care. This corresponds with the findings of Katz, Holland and Peace, namely that elderly persons with high support needs are most concerned with getting through the day.…”
Section: Discussionmentioning
confidence: 80%